IMPLEMENTASI PROGRAM PENGEMBANGAN DIRI ANAK BERKEBUTUHAN KHUSUS SDN SUMBERSARI 2 KOTA MALANG - Ogie Zerlinda Yumna; Bustanol Arifin; Murtyas Galuh Danawati (Institut Pendidikan Tapanuli Selatan, 2024)
The implementation of the self-development program for children with special needs at SDN Sumbersari 2, Malang City has been running from August 2023 until now. Self-development program aimed at children with special needs for grades 1-6 elementary school. Implementing self-development is the ability to develop motor skills, concentration, creativity, independence and social abilities. The aim of this study: (1) to describe self-development activities in the implementation of self-development for children with special needs at SDN Sumbersari 2 Malang City (2) to describe the implementation of the self-development program for children with special needs at SDN Sumbersari 2 Malang City (3) to describe the impact of students in implementing the self-development program children with special needs at SDN Sumbersari 2, Malang City. This research is descriptive qualitative research. The subjects of this research were the principal of SDN Sumbersari 2 Malang City, teacher coordinator of the self-development program and Shadow. The implementation of the self-development program was attended by 12 children with special needs, one of whom had ADHD. To obtain the necessary data, research is needed using observation, interview and documentation techniques. The research results obtained are that shadow guides the implementation of self-development, preparing students for carrying out different self-development activities such as collage, painting, cooking classes, making creativity from bottle caps. In implementing self-development, there is an impact of each implementation of self-development to train fine motor skills, concentration, creativity and independence.